A CASE REPORT OF ZIDOVUDINE-INDUCED THUMBNAILS HYPERPIGMENTATION IN AN HIV POSITIVE PATIENT WITH SECONDARY HERPES ZOSTER OPHTHALMICUS INFECTION - TIRIN BABU; GEORGE MATHEW PANACHIYIL; JUNY SEBASTIAN; VEERANNA SHASTRY (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Zidovudine is one of the first-line antiretroviral therapy regimen drug used to treat human immunodeficiency virus infected patients. Nail pigmentation associated with zidovudine therapy is seen in adults and children’s, mainly dark-skinned patients. This case attempts to draw attention among healthcare professionals concerning the non-serious adverse effect of nail pigmentation with zidovudine. In our case, the patient was counseled about this adverse effect without any change in zidovudine therapy. Even though this side effect is harmless and reversible, the psychological aspects of this visible side effect may reduce medication adherence and can also result in inessential investigations and management for misdiagnoses such as cyanosis and melanoma.